The Impact of Tourism Development on Socio-Economic Conditions for Coastal Communities in Lasiana Beach, Kupang City - Ariawan, I Wayan Adi Putra; Sanam, Syul Rosli; Jehane, Protasius Tiberius; Riwu, Oktovianus Udju (Jurnal Manajemen Pelayanan Hotel, 2024)
Lasiana Beach is one of the tourist attractions that has become a prime destination due to its natural beauty, located in Lasiana Village, Kupang City. The tourism development at Lasiana Beach is supported by various stakeholders involved, such as the government, the local community, and academics who continuously research to promote sustainable tourism at Lasiana Beach. This is evidenced by data from the East Nusa Tenggara Provincial Tourism and Creative Economy Office, which indicates that the number of tourist visits to Lasiana Beach has consistently increased each year. The growth of tourism at this attraction presents opportunities for the surrounding coastal community to capitalize on the ongoing tourism development. The challenges faced in the tourism development at the Lasiana Beach attraction include the lack of studies assessing the extent of the social and economic impacts on the coastal community of Lasiana Beach. Despite various efforts made by the local government to enhance tourism in the area, it remains unclear how far-reaching the resulting impacts have been. This research was conducted at Lasiana Beach in Kupang City using a qualitative descriptive method. The results of this study were analyzed based on indicators of socio-economic impact, such as the increase in community income, public health, population growth, labor absorption, and the development of the economic structure, which is characterized by economic activities arising from projects such as food stalls, restaurants, transportation services, shops, and others.